2014
DOI: 10.1007/s00330-014-3210-1
|View full text |Cite
|
Sign up to set email alerts
|

Arterial hyperintensity on BLADE fluid-attenuated inversion recovery images (FLAIR) in hyperacute territorial infarction: comparison with conventional FLAIR

Abstract: Arterial hyperintensity is an important sign in patients with acute territorial infarctions. BLADE FLAIR sequences are sensitive for the detection of AH. BLADE FLAIR sequences provide better image quality by reducing artefacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Recently, Kwag et al reported that the PROPELLER technique enhanced the FHV sign in acute MCA stroke patients (20). Our results also showed that PROPELLER technique strongly enhanced the degree of FHVs.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Recently, Kwag et al reported that the PROPELLER technique enhanced the FHV sign in acute MCA stroke patients (20). Our results also showed that PROPELLER technique strongly enhanced the degree of FHVs.…”
Section: Discussionsupporting
confidence: 81%
“…The PROPELLER technique has been implemented with conventional MR sequences to reduce motion artifacts and increase image quality (17)(18)(19). Recently, Kwag et al reported that the PROPELLER technique enhanced the FHV sign in acute MCA stroke patients (20). Our results also showed that PROPELLER technique strongly enhanced the degree of FHVs.…”
Section: Discussionsupporting
confidence: 63%
“…Gawlitza et al 23 reported that there was significant correlation between the degree of the FHV sign and PWI lesion volume, but they did not compare FHV signs with PWI territory by territory. Kwag et al 24 recently…”
Section: Discussionmentioning
confidence: 98%
“…Although the difference in parameters may be trivial, this might have changed the appearance of HVs. 21…”
Section: Discussionmentioning
confidence: 99%